The role of cytokines from salivary gland epithelial cells in the immunopathology of Sjögren’s syndrome - Dong, Yuanji; Wang, Ting; Wu, Huaxiang (Frontiers in Immunology, 2024)
In the pathogenesis and progression of Sjögren’s syndrome (SS), hematopoietic cells in the peripheral circulation, tissue-resident immune cells, and parenchymal cells of salivary gland tissues (such as epithelial cells, endothelial cells, fibroblasts, etc.) all play crucial roles. These diverse cells form intricate networks and interact with each other, leading to tissue destruction and persistent chronic inflammation, ultimately causing irreversible damage in glandular function. Among these, salivary gland epithelial cells (SGECs) consistently hold a key position, characterized by their functions in expressing co-stimulatory and antigen-presenting molecules and secreting pro-inflammatory cytokines and chemokines. Moreover, SGECs actively engage in and facilitate the development of specific pathological structures within the salivary gland, such as lymphoepithelial lesions (LELs) and tertiary lymphoid structures (TLSs), thereby substantially elevating the risk of mucosa-associated lymphoid tissue (MALT) lymphoma. Overall, SGECs are recognized for their essential and irreplaceable contributions to the pathogenesis of SS. This review article initially delves into the anatomical composition of salivary gland epithelial cells, subsequently focusing on elucidating the different cytokines derived from SGECs, encompassing chemokines, pro-inflammatory cytokines, anti-inflammatory cytokines, pro-survival cytokines, and damage-associated molecular patterns (DAMPs), to explore their key roles in the pathogenesis of SS.